The Influence of Features and Promotions on Wondr Bni Usage With User Satisfaction as Intervening - Sri Indayani; Syarida Hafni Sahir; Minda Muliana Br Sebayang (Universitas 17 Agustus 1945 Semarang, 2025)
This research aims to determine the effect of service features and promotions on increasing users of Wondr by BNI services with user satisfaction as an intervening variable. This type of research is quantitative. The population in this study were BNI customers of the Medan Industrial Estate Branch Office who were registered and had used the new digital service application WONDR by BNI. The total population was 16,769 customers with a sample of 391 respondents. Data was collected by questionnaire with a Likert scale, validity testing, reliability and hypothesis testing were carried out using SmartPLS ver 4.0 software. The results show that service features have a significant direct effect on user satisfaction, service features have a direct effect on increasing the number of users, promotion has a direct effect on user satisfaction, promotion has a direct effect on increasing the number of users, user satisfaction has a direct effect on increasing the number of users, service features have an indirect effect on increasing the number of users through user satisfaction as an intervening variable, promotion has an indirect effect on increasing the number of users through user satisfaction as an intervening variable. These findings indicate that user satisfaction plays an important role in strengthening the effect of service features and promotions on increasing the number of service users. Therefore, to sustainably increase the number of users, Wondr by BNI needs to optimize service features that are responsive to user needs and implement promotional strategies that can increase user satisfaction and loyalty.